Climate Change in Asia and Africa Examining the Biophysical and Social Consequences, and Society's Responses - Tiefenbacher, John P. (IntechOpen, 2022)
This volume contains studies of the implications of changing climates in Asia and Africa, two regions containing the majority of Earth's population and many less developed countries. People of this region often lack the cushion of advanced technologies or economic safety nets that the West has come to expect. The region has significant resource-development challenges, particularly for food production. The consequences of changing climates for the natural and human environments in this region are different in their social and economic contexts. The challenges are often complicated by a lack of data and lack access to relatively common technological systems that enable monitoring, field work, management, and mitigation. This book contains three parts that focus on the biophysical and social consequences of changing climates and progress toward adaptation and mitigation to change. There are studies on evapotranspiration rates in North Africa, precipitation extremes in Asia, coral bleaching in the Indian Ocean, the patterns of humid-region flood risk and hazards in Asia, the implications of climate change for Zimbabwe's horticultural sector, agricultural vulnerability in Uganda, mitigation and adaptation on palm-oil plantations in Indonesia, the value of farmer's knowledge for mitigating precipitation variability in eastern and southern Africa, sustainable carbon management in paddy rice-growing regions, adaptation to changing patterns of hazards in India, river flooding and temporary displacement of women and children of Nigerian villages, and management and mitigation of ecological impacts and diversity in Nepal.